Zweite Zeitgenössische Ungarische Epigonen Ausstellung. - Haas, Mechthild; Vogel, Christian; Várnagy, Tibor; Wucher, Monika (Hamburg : Projektförderung Bildende Kunst, 1993)
Adám, Zoltan ; Bernát, András ; Beöthy, Balázs ; Bogdány, Dénes ; Bolvári, Csaba ; Böröcz, András ; Durst, György ; Elek, Is ; Eperjesi, Agnes ; Füsti, Kristóf ; Gerhes, Gábor ; Gulyás, Agnes ; Halas, István ; Hecker, Péter ; Kecskés, Péter ; Keesmeyer, Michael ; Kingsley, Diana ; Koroknai, Zsolt ; Kovács, Lóránd ; L., László Révész ; Lavman, Maria ; Lengyel, András ; Litván, Gábor ; Lévay, Jenö ; Medve, András ; Menesi, Attila ; Nagy, Attila ; Nagy, Sándor Bodó ; Nemes, Csaba ; Pacsika, Rudolf ; Peternák, Miklos ; Ravasz, András ; Sugar, Janos ; Swierkiewicz, Róbert ; Szarka, Péter ; Szili, István ; Szöveges, Katalin ; Szücs, Attila ; Tnpu ; Tolvaly, Ernö ; Tóth, Gábor ; Vetö, János ; Várnagy, Tibor ; Várnai, Gyula
Duits
Zweite Zeitgenössische Ungarische Epigonen Ausstellung, K.X. Kunst auf Kampnagel, Hamburg 7.12.1993 - 9.1.1994
boek
Keywords: Hongarije